2022
DOI: 10.33448/rsd-v11i11.34058
|View full text |Cite
|
Sign up to set email alerts
|

Microwave assisted pyrolysis of expanded polystyrene waste using carbon black catalyst

Abstract: Polymeric materials are increasingly present in everyday life and are discarded on a large scale constituting a challenge for its recycling. This work studied the depolymerization of expanded polystyrene (EPS) waste through microwave using carbon black as catalyst. The catalytic pyrolysis was investigated at five catalysts to polymer ratios (0.0125:1, 0.125:1, 0.25:1, 0.5:1, 1:1). The microwave assisted pyrolysis occurred at 400 W in a fixed time of 12 minutes. Fourier Transform Infrared Spectroscopy (FTIR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The results shows that GO is an efficient catalyst to promote EPS depolymerization in low microwave exposition time. In a previous study, Marco and Poletto (2022) using the same apparatus, but with carbon black catalyst, obtained a gaseous fraction of approximately 54% using a exposure time three times higher.…”
Section: Microwave Assisted Pyrolysis Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The results shows that GO is an efficient catalyst to promote EPS depolymerization in low microwave exposition time. In a previous study, Marco and Poletto (2022) using the same apparatus, but with carbon black catalyst, obtained a gaseous fraction of approximately 54% using a exposure time three times higher.…”
Section: Microwave Assisted Pyrolysis Resultsmentioning
confidence: 94%
“…To avoid heat loss the quartz flask was insulated with mineral wool and all joins were sealed using Teflon tape. The experimental setup used in this work is based on a previously published work (Marco and Poletto, 2022).…”
Section: Microwave Assisted Pyrolysismentioning
confidence: 99%
See 2 more Smart Citations
“…Going further, many researchers have made several attempts to use the pyrolysis processes in recycling the expanded polystyrene waste. de Marco, Poletto [53] attempted to depolymerize expanded polystyrene through microwaveassisted pyrolysis using a carbon black catalyst. Their studies revealed pyrolysis of expanded polystyrene at 400W in a fixed time of 12 minutes.…”
Section: Thermal Recyclingmentioning
confidence: 99%